Phytosterol Profile in Iraqi Lactuca serriola after Purification and Isolation by Combiflash and HPLC (Conference Paper )# - Murtadha Saleh Hussien; Ayad A. Al-Hamashi (Iraqi Journal of Pharmaceutical Sciences, 2023)
One of these plants utilized in traditional medicine is Lactuca seriolla Linn., which belongs to the Asteraceae family. It goes by a variety of common names in the world, including prickly lettuce, wild lettuce, jagged lettuce, and Kahu and khas. The work aimed to isolate and characterize some bioactive constituent(s) from the aerial part of Lactuca serriola utilizing  Combiflash NEXTGEN and high-performance liquid chromatography (HPLC). Lactuca serriola (aerial part) was extracted with 80% ethanol, then fractionated with hexane. Then 250 mg of hexane extract was mixed with 4 g of silica gel and loaded in cartilage, then bounded to the gold column of combi flash using a solvent system comprised of ethyl acetate: n-hexane (10% ethyl acetate 90% hexane v/v) to elute the column. The fractions resulting were analyzed by thin layer chromatography and high-performance liquid chromatography (HPLC). white needle-like crystalline substances were isolated via combi flash column chromatography. The isolated product was analyzed by thin layer chromatography and high-performance liquid chromatography (HPLC). β-sitosterol (11 mg) and stigmasterol (7 mg) were obtained from 250 mg of hexane fraction.